"Administrative feasibility analysis" for development projects concept and approach - Whang, In-Joung (1978)
There is an emerging need for the integration of planning and implementation of development projects into one conceptual framework. To meet this, administrative
feasibility analysis or the appraisal of administrative systems and managerial factors
should be introduced as a complementing step in the project feasibility study to
strengthen the planning function by which the implementability of the project could
be assessed ahead of its selection. Since this analysis tends to be neglected by policy
makers and planners, the preparation of the necessary administrative inputs for an improved project implementation should be taken after the selection but before activation. In this context, administrative feasibility analysis can be viewed as: (a) an integral part of the appraisal criteria in the project selection and as (b) a benchmark study for implementation support planning for project implementation. Finally, since administrative feasibility analysis requires an overall analysis of all the administrative factors involved in project management, its institutionalization would require a systematic program to produce the needed expertise in the project.
Keywords: Public administration -- Research; Feasibility studies